2019
DOI: 10.1038/s41385-019-0207-8
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section increases sensitivity to oxazolone-induced colitis in C57BL/6 mice

Abstract: Children born by cesarean section (CS) have an increased risk of developing inflammatory bowel disease (IBD), possibly due to skewed microbial colonization during birth and consequently impaired bacterial stimulation of the developing immune system. The aim of this study was to investigate the association between CS and experimental colitis in a murine model of IBD. It was hypothesized that CS aggravates colonic inflammation due to a change in gut microbiota (GM) composition. C57BL/6 mice, delivered by CS or v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
(62 reference statements)
0
11
0
Order By: Relevance
“…These immunological effects can be transferred by inoculation of germfree mice with fecal samples from cesarean section-born mice. Furthermore, cesarean section delivery performed in germ-free mice, where the mice were kept germ-free, did not show these immunological effects, again implicating gut microbial differences (31,32). During episodes of acute airway symptoms occurring in our cohort among children between 1 and 4 years of age, we observed that children with a high cesarean section gut microbial score at age 1 year had an overall lower airway immune response.…”
Section: Cesarean Section Microbial Scorementioning
confidence: 61%
“…These immunological effects can be transferred by inoculation of germfree mice with fecal samples from cesarean section-born mice. Furthermore, cesarean section delivery performed in germ-free mice, where the mice were kept germ-free, did not show these immunological effects, again implicating gut microbial differences (31,32). During episodes of acute airway symptoms occurring in our cohort among children between 1 and 4 years of age, we observed that children with a high cesarean section gut microbial score at age 1 year had an overall lower airway immune response.…”
Section: Cesarean Section Microbial Scorementioning
confidence: 61%
“…Caesarean sections may increase sensitivity to colitis, 56 probably due to the microbiota‐regulated reduction in Treg cells and an increase in iNKT cells 57 or due to the influence on the colonisation of commensal flora in the gut 58 . A previous study demonstrated that the risk of CD, but not UC, was higher in patients who underwent caesarean delivery (OR = 1.38) 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In an oxazolone colitis model, CSD mice were more sensitive to the treatment than VD mice, including higher concentrations of TNF-alpha and inflammation markers in the colon. This phenotype was transferred to germ-free mice when inoculated with CSD and VD mouse microbiota [52]. A murine model has shown social, cognitive, and anxiety deficits, both in early life and adulthood.…”
Section: Higher Risk Of Leukemia and Lymphoblastic Leukemiamentioning
confidence: 99%